Towards more pedestrian-friendly streets in Cairo - El Ghandour, Sahar Ahmed Zaki (AUC Knowledge Fountain, 2016)
This research explores the factors that make the streets of Cairo better places for walking, more inviting, and adaptable to be used by pedestrians. In order to closely examine how far Cairo streets are pedestrian-friendly, walkable environments, the research investigates one street in Cairo as a case study. The case study uses qualitative research to investigate the street characteristics through participants’ observation technique, while the local pedestrians’ needs and perceptions towards the street’s walkability are explored through interviews. In addition, an in-depth interview is conducted with an expert in order to have deeper insights into the issue of pedestrian-friendly streets from a professional perspective. The existing models reviewed through the literature have contributed to the development of the proposed conceptual framework. The study’s empirical findings have shown that safety and cleanliness of streets are the main factors that influence people’s walking experience. Besides, pavement and sidewalks conditions, street furniture and lighting, along with other street user’s behavior, such as car drivers and shopkeepers, are other factors that implicitly and/or explicitly affect street walkability. The analysis of the findings contributes to the limited qualitative research on walkable streets and pedestrians’ walking experience specifically in Cairo. Thus, this study offers a set of recommendations for policy makers and city managers in terms of conducting further research that covers other geographic areas in Cairo, adopting a participatory planning approach, enforcing laws and regulations on street occupancy, applying people-oriented planning paradigms, and raising public awareness on walkability.